Analisis Nilai Tambah Keripik Singkong UKM Mandiri Kabupaten Mojokerto - Novita, Mega D.; Saifuddin, Akhmad (Agriculture and Socio-Economic Journal, 2024)
This research aims to know the value of added, efficiency and profit from the processing of cassava chips into cassava in Tampung Rejo village of Puri District Mojokerto The research method used is a descriptive analytical method. This research is done purposive (intentionally) in UKM. Mandiri  District Puri District Mojokerto. The method of determination of respondents was done by census techniques against 5 respondents (producers). The data used is primary data and secondary data with observation, interviews and recording. The data analysis methods used are business analysis to know the magnitude of added value, efficiency and profitability. The results showed that the profits received from the processing business of cassava into cassava chips in one time production process of Rp. 1.272.197,-. Business efficiency of 1.715. The processing of cassava into cassava chips gives an average gross added value of Rp. 1.485.100,-, the average net added value of Rp. 1.482.196,-, Value added per raw material amounting to Rp. 5.550,-/kg and added value per workforce of Rp. 50.823,-/JKO.